Gerenciamento de resultados e remuneração dos executivos nas companhias latino-americanas - Santana, Alex Fabiano Bertollo (Universidade do Vale do Rio do Sinos, 2008)
The objective of this study was to determine whether the forms of compensation for executives of companies Latin American influence earnings management. There was an empirical analysis of 48 companies, of 4 different Latin American countries in a period of 5 years (between 2002 and 2006), which totaled of 240 observations. To check the occurrence of earnings management in Latin American companies, the model adopted was Kang and Sivaramakrishnan (1995). The statistical tests used to the validity of regressions were: Mann-Whitney U test and Wald. The findings the study showed signs of greater level of earnings management in companies that ofter variable pay to their executives.
Keywords: accruals discricionários; remuneração dos executivos; gerenciamento de resultados; discretionary accruals; executive compensation; earnings management; Ciências Sociais Aplicadas